Antioxidant properties of Etlingera pubescens, an edible ginger plant endemic to Borneo. (October 2018) - Daniel-Jambun, Delhousie; Ong, Kuan Shion; Lim, Yau Yan; Lee Tan, Joash Ban; Lee, Wai Leng; Muhamad, Azira; Yap, Sau Wai; Lee, Sui Mae
Abstract: Zingiberaceae is a family that consists of many edible ginger plants. Etlingera pubescens (B.L.Burtt & R.M.Sm.) R.M.Sm. was studied for its antioxidant properties. Preliminary screening of the methanol extracts of its leaves, stems, rhizomes showed that the fresh leaves had the highest antioxidant activity, with total phenolic content (TPC), ascorbic acid equivalent antioxidant capacity (AEAC), and oxygen radical absorbance capacity (ORAC) values of 1020 ± 20 mg GAE/100 g, 1130 ± 30 mg AAE/100 g, and 140 ± 30 µmol TE/g, respectively. Subsequently, a diarylheptanoid, etlingerin, was isolated from the leaf methanol extract. When contrasted with curcumin (a well-known diarylheptanoid), etlingerin showed comparable free radical scavenging properties. However, using a cell-based antioxidant assay, etlingerin showed significantly better protective effects (with cellular antioxidant activity values as high as 84 ± 4%) than curcumin at all concentrations tested. In the cytoprotective study, only etlingerin could protect cells that were challenged with hydrogen peroxide. These effects might be explained by etlingerin's high lipophilicity and good free radical scavenging properties. Etlingerin was also found to be significantly less cytotoxic than curcumin (up to 10-fold, as determined using a MTT cell viability assay), thus suggesting its safety. The work showed that etlingerin has better antioxidant properties, hence highlighting its potential as a functional food component that could reduce the risks of oxidative stress-related diseases.